PENGUJIAN BRAND SATISFACTION TERHADAP EMOTIONAL BRAND ATTACHMENT, BRAND LOYALTY, BRAND LOVE, DAN SELF ESTEEM PRODUK SNEAKERS DI INDONESIA - Armenia, Monica Desty; Kurniawati, Kurniawati (Universitas Nusa Cendana, 2024)
The sneaker industry has witnessed remarkable growth in recent years, accompanied by a surge in new brands, intensifying the battle for customer loyalty. This study delves into the intricate relationship between brand satisfaction and its impact on emotional brand attachment, brand love, brand loyalty, and self-esteem among sneaker enthusiasts. Data was collected from 255 sneaker users through an online survey administered using Google Forms to explore these connections. Purposive sampling was employed, targeting individuals who actively wear sneakers. The Structural Equation Model (SEM) was utilized to analyze the gathered data, leveraging the AMOS 22 software. The findings unveil a significant positive influence of brand satisfaction on emotional brand attachment. Additionally, brand satisfaction demonstrates a positive impact on brand loyalty and brand love. Emotional brand attachment, in turn, exhibits a positive influence on brand love and brand loyalty. Furthermore, self-esteem emerges as a positive contributor to brand loyalty. These findings underscore the crucial role of brand satisfaction in fostering positive customer perceptions and behaviors, particularly in the competitive sneaker industry. By cultivating brand satisfaction, companies can strengthen emotional brand attachment, brand love, and brand loyalty, ultimately enhancing customer self-esteem and establishing a loyal customer base. Keywords : Brand Satisfaction; Emotional Brand Attachment; Brand Love ; Brand Loyalty; Self-esteem